ANALISIS TERHADAP SENGKETA ANTI-DUMPING PRODUK KERTAS INDONESIA DENGAN KOREA SELATAN - Riyani Kusuma Yekti; Naila Alya Ramadhini; Zahrah Maydina Salma; Aqilatun Nafisah (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Abstract Economic relations in terms of trade between countries will always cause obstacles in diverse forms, one of the forms is the practice of dumping. This practice can cause losses for a country and trigger disputes between the countries concerned. In this research, the author will discuss a dispute about allegations of paper products from Indonesia that are considered to include dumping practices committed by South Korea. This research will focus on the Indonesian government's strategy in resolving the dispute and the legal process between Indonesia and South Korea. In resolving this dispute, South Korea has not completely gone through with the decisions of the Dispute Settlement Body (DSB) in 2005 and 2007. Indonesia government called on the South Korean government to go through with the last decisions of the Dispute Settlement Body by using strategies such as retaliation plans also the forcing of Anti-Dumping Duties (ADD) imposed on all South Korean paper producers concerned. To resolve the issue, the South Korean government decided to take legal action through the Korea Trade Commission (KTC) by formally revoking the Anti-Dumping Duties. This decision marks a major success and victory for Indonesia in the world trade organization. Abstrak Hubungan ekonomi dalam hal perdagangan antarnegara akan selalu menimbulkan terjadinya hambatan dalam berbagai bentuk, salah satunya adalah praktik dumping. Praktik ini dapat menyebabkan kerugian bagi suatu negara dan memicu terjadinya perselisihan antarnegara yang bersangkutan. Pada penelitian ini, penulis akan membahas sengketa tentang tuduhan produk kertas dari Indonesia yang dianggap termasuk praktik dumping yang dilakukan oleh Korea Selatan. Penelitian ini akan berfokus pada bagaimana strategi Pemerintah Indonesia dalam menyelesaikan perselisihan dan proses hukum antara Indonesia dengan Korea Selatan. Dalam penyelesaian sengketa ini, Korea Selatan belum sepenuhnya menerapkan putusan dari Dispute Settlement Body (DSB) pada tahun 2005 dan 2007. Pemerintah Indonesia meminta pemerintah Korea Selatan untuk melaksanakan keputusan akhir yang telah diputuskan Dispute Settlement Body dengan menggunakan strategi seperti rencana pembalasan dan pengenaan Bea Masuk Anti-Dumping (BMAD) bagi seluruh produsen kertas Korea Selatan yang bersangkutan. Untuk menyelesaikan isu tersebut, pemerintah Korea Selatan memutuskan mengambil tindakan hukum melalui Korea Trade Commission (KTC) dengan secara resmi mencabut Bea Masuk Anti-Dumping. Keputusan ini menandai keberhasilan dan kemenangan besar Indonesia di organisasi perdagangan dunia.